Extended Spectrum Beta-Lactamase (ESBL) - Verna Biutifasari (Universitas Hang Tuah, 2018)
Antibiotics have been widely used today. Use of antibiotics is also often used in mass and not in accordance with the indication, among others, in a particular case of fish poisoning on the beach, often the treatment is given antibiotics without clearlyindication. Use of antibiotics are excessive and not in accordance with the clinical, can cause resistance to these antibioticsOne of the antibiotics used is a beta-lactam antibiotic, that works inhibits cell walls. The inappropriate use of beta-lactam antibiotics can lead to resistance to these antibiotics. Resistance to beta-lactam can occur at various levels. One of the resistances can occur is resistance to Extended Spectrum Broad Lactamase (ESBL)Extended spectrum beta-lactamase is an enzyme that has the ability to hydrolyze penicillin-type antibiotics, first-generation cephalosporins, two, and three as well as monobactam groups and cause resistance throughout the antibiotic.ESBL is produced by many Enterobactericeae (especially Escherichia coli) and Klebsiella pneumoniae. Enterobacteriaceae has 3 resistance patterns caused by broadspectrum beta-lactamase, beta-lactamase-resistant inhibitors (TEM derivatives), excessive cephalosporinase. ESBL can be difficult to detect because ESBL has differentiatedactivity to various cephalosporinsESBL can be detected in clinical microbiology (phenotypic) and molecular detection (genotypic)